Integrating Meaningful, Mindful, and Joyful Learning in Pedagogical Deep Learning-Based ELT Lesson Plans - Idris, Bayu Romli; Purwaning, Alynia; Sumantri, Kun; Ratih, Koesoemo; Fauziati, Endang (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2026)
Pedagogical deep learning has become an important orientation in ELT/TESOL because it encourages language teaching to move beyond surface-level activities toward conceptual understanding, reflective engagement, purposeful participation, and transferable language use. However, previous studies have often examined meaningful, mindful, and joyful learning separately, leaving limited evidence on how these three dimensions are jointly translated into English lesson planning, particularly in the alignment of objectives, instructional scenarios, and assessment. This study aims to analyze the patterns of integration of meaningful, mindful, and joyful learning in English lesson plans, identify imbalances in instructional design and assessment, and explain the forms of metacognitive assessment used or not yet used by teachers. Employing a qualitative multiple-case study design, the research analyzed six English lesson plans from elementary, junior high, and senior high school levels. The document analysis was supported by semi-structured interviews with four English teachers from three schools, consisting of two novice teachers with fewer than five years of teaching experience and two experienced teachers with more than ten years of service. The data were analyzed thematically through repeated reading, coding, within-case analysis, and cross-case comparison. The findings show that meaningful learning was the most visible dimension, mainly through contextualized topics and communicative tasks; mindful learning was the weakest dimension because reflective and metacognitive assessment was limited; and joyful learning was unevenly integrated, ranging from purposeful participation to entertainment detached from learning goals. The study concludes that deep learning in ELT requires coherent alignment among essential content, learning objectives, learning activities, and reflective or metacognitive assessment.